2007
DOI: 10.1093/humrep/dem326
|View full text |Cite
|
Sign up to set email alerts
|

Human decidual stromal cells express HLA-G Effects of cytokines and decidualization

Abstract: Our results suggest the existence of a network in which hormones together with cytokines regulate the expression of HLA-G by DSC, and that may be of relevance in the maintenance of maternal-fetal tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 43 publications
4
57
0
3
Order By: Relevance
“…IFN␥ production by peripheral lymphocytes in very early pregnancy is higher in normal women compared with women with recurrent miscarriage. 42 By contrast, IL-10 is known to be an antiinflammatory cytokine, 45 and as shown in our study and others, 46,47 high levels of IL-10 are associated with successful outcome. We also found that, when the ratios of Th1/Th2 cytokines were calculated, there was a shift towards Th1 cytokines with elevated TNF␣/IL-10 and IFN␥/ IL-10 ratios in patients with TM who subsequently miscarried.…”
Section: Commentsupporting
confidence: 65%
“…IFN␥ production by peripheral lymphocytes in very early pregnancy is higher in normal women compared with women with recurrent miscarriage. 42 By contrast, IL-10 is known to be an antiinflammatory cytokine, 45 and as shown in our study and others, 46,47 high levels of IL-10 are associated with successful outcome. We also found that, when the ratios of Th1/Th2 cytokines were calculated, there was a shift towards Th1 cytokines with elevated TNF␣/IL-10 and IFN␥/ IL-10 ratios in patients with TM who subsequently miscarried.…”
Section: Commentsupporting
confidence: 65%
“…IL-10 was demonstrated to increase both HLA-G mRNA and cell surface protein expression by monocytes [45], mesenchymal stem cells [50], renal cell carcinoma (RCC) cell lines [51] and human decidua stroma cells [52], and also soluble HLA-G protein by mononuclear cells from patients suffering from non-Hodgkin lymphomas (T-NHL) [53], acute myeloblastic leukaemia (AML) and acute lymphoblastic leukaemia (B-ALL) [52]. Moreover, a reduced placental IL-10 production was observed in preeclampsia [54] and correlates with a low level of expression of HLA-G transcription [38,55].…”
Section: Cytokines Growth Factors and Hormonesmentioning
confidence: 99%
“…28 It has been hypothesized that HLA-G is one of the most important tolerogenic molecules during pregnancy. Although HLA-G is preferentially expressed at high levels in trophoblasts, it is also expressed by decidual stromal cells (the major cellular population in human decidua), 29 DC-10, CD4 1 T cells 26 and DC-SIGN 1 iDCs. 21 Stromal cell expression contributes to tolerance, not only because of their expression on the decidua but also via their interaction with dNK cells.…”
Section: Human Dcsmentioning
confidence: 99%